Analysis of socioeconomic indicators of rural properties in Nova Esperança do Sudoeste – PR (International Seven Journal of Multidisciplinary, 2023)
The income generation in the agricultural and cattle raising activities is intrinsically linked to the economic, social and environmental aspects. In this sense, seeking to understand the generation of income, we studied eight rural properties in the municipality of Nova Esperança do Sudoeste - PR, relating quantitative indicators of Gross Product (GP), Intermediate Consumption (IC) and Agricultural Income (AR). This analysis used the variables produced by the extension project and discipline Rural Property Planning which is practiced in academic and social environment in the agronomy course of the Federal Technological University of Parana, Dois Vizinhos Campus, whose methodology is divided into three main parts: diagnosis, rural planning and feedback to rural producers. In this context, it was used information about the production systems of the properties mostly focused on dairy production, agricultural area, PB/ha, CI/ha, RA/ha and two indexes calculated by contrasting the indicators (RA /CI (ha)(ha)) and (RA / PB (ha)(ha)). In this analysis, we noted different income generation strategies, differentiated by the degree of investment with inputs, where in general, the properties that invested more, obtained a better return, with exceptions in which the gross wealth produced was not consistent with the amount invested, generating economic inefficiency of the activity.